Extracting structural information of higher coordination shells by analyzing EXAFS derivative spectrum. (26th October 2018) - Chen, Tao; Chu, Shengqi; Zhou, Xiaojuan; Zheng, Lirong; An, Pengfei; Lin, He; Zhang, Jing; Hu, Tiandou
Abstract: A method has been developed for analyzing the extended x-ray absorption fine structure (EXAFS) derivative spectrum. Taking Fourier transform to EXAFS derivative spectrum data can enhance the signal of high coordination shells. The EXAFS spectroscopy of high-purity Ge powder is taken as an example to present the whole data processing procedure. Through the comparison of the pair distribution function approach and the normal EXAFS analysis, we confirm the reasonableness and the effectiveness of the method. Particularly, this EXAFS derivative method may be a useful tool for studying the relatively high coordination shells in materials.